Integration of Kano’s Model and SERVQUAL into House of Quality (HOQ) for Developing QMS Training Program - Saadon, Mohd Saiful Izwaan; Mustafa, Zainol; Mohamed Nor, Dina Azleema (Journal of Technology Management and Business, 2014)
Quality Management System (QMS) is a very important knowledge that is very crucial in any industrial organization. It is very important for the industrial workers to know and understand the correct QMS knowledge & concept. Because of that it is very important for them to attend sufficient and relevant QMS training in order for them to attain the QMS knowledge. These training must be effective and have sufficient impact. For that purpose a new method is used in this research. The Kano’s Model and SERVQUAL are integrated into the House of Quality (HOQ) for the purpose of developing a QMS training course that would not only satisfy the requirement and needs of the industry but also unexpected factors towards the trainee who attended the course. By using this method we can see that the level of understanding for the training participant using this new model is higher compared to the level of understanding for the participant from the conventional QMS training program that had been conducted by the training provider. With the increment in the level of understanding the level of effectiveness for doing QMS related jobs for the training participant would also be different. We can prove this by using the Kirkpatrick’s Evaluation Model, whereby we would evaluate the trainee from the conventional QMS training program against the newly developed QMS training program. The evaluation would be based on their level of understanding and the level of effectiveness of doing QMS related jobs in their respective workplace.